Inactivation of Treponema pallidum by Silver Sulfadiazine - Chang, Te-Wen (1975)
Silver sulfadiazine, an anti-infectious agent for the prevention and treatment of burn sepsis, has been found to possess antitreponemal activity against Treponema pallidum. At 28 C, complete inactivation of the organism was produced by exposure of the organism to a concentration of 50 μg of the drug per ml for 1 to 5 min, 12 to 25 μg/ml for 10 to 15 min, and 6.2 μg/ml for 30 min. At 37 C, the amounts of silver sulfadiazine required for inactivation were two- to fourfold less.